The Incidence of Rates on Houses - Fogarty, M. P. (Review of Economic Studies, 1943)
Journal Article The Incidence of Rates on Houses Get access M. P. Fogarty M. P. Fogarty Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 10, Issue 2, Summer 1943, Pages 81–105, https://doi.org/10.2307/2967426 Published: 01 July 1943